(untitled) (Strathmore Law Journal, 2020)
Lawfare is a term that is truly base, common and popular. From a commercial catchword used by travel agencies to sell cheap airfares to lawyers, to a deprecatory word for the ‘individualistic and accusatorial aspects of law in Western societies,’ to the descriptor of joining transnational organisations in order to subvert the interpretations of law, to delegitimising strategies of weak actors in international forums who turn the law against the just and powerful actors, lawfare has multiple meanings depending on the context of its use. Yet for all its ordinary, contradictory and evolving usage, lawfare is amenable to principled definition, practical elaboration and strategic utilisation for national security.